Looking for Lakshmi - Soni, Rajan (My University, 2008)
The research project presented here draws on aspects of memoir, biography and travel writing to fashion a narrative best placed in the emergent frame of life-writing. It is the story, real and allegorical, of my search for an anonymous paternal Indian grandmother who died before I was born on an island colony off the coast of British East Africa. Two themes echo through the narrative: the enigmatic call of my father’s abiding silence about his mother; and the existential angst of my search for identity as the closed Diasporaic Indian community of my childhood dissolved with the political and cultural changes wrought by Kenya’s Independence. These inner and outer journeys are woven together into a quest that examines the representational allure of a remote and mythical grandmother, alongside the formation and fragmentation of identity in the face of migrations from landscapes of birth, to imaginary notions of home.
Keywords: life-writing; Indian Ocean Studies; memoir; biography; travel writing; historiography